Evolution of research subjects in library and information science based on keyword, bibliographical coupling, and co-citation analyses - Chang, Yu-Wei; Huang, Mu-Hsuan; Lin, Chiao-Wen (Scientometrics, 2015)
This study involved using three methods, namely keyword, bibliographic coupling, and co-citation analyses, for tracking the changes of research subjects in library and information science (LIS) during 4 periods (5 years each) between 1995 and 2014. We examined 580 highly cited LIS articles, and the results revealed that the two subjects “information seeking (IS) and information retrieval (IR)” and “bibliometrics” appeared in all 4 phases. However, a decreasing trend was observed in the percentage of articles related to IS and IR, whereas an increasing trend was identified in the percentage of articles focusing on bibliometrics. Particularly, in the 3rd phase (2005–2009), the proportion of articles on bibliometrics exceeded 80 %, indicating that bibliometrics became predominant. Combining various methods to explore research trends in certain disciplines facilitates a deeper understanding for researchers of the development of disciplines.